(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
Since phraseologisms are based on nationality, their translation is always difficult and often causes serious problems. Usually their content is translated, not only their form. This article is illustrated to the analysis of translation of phraseological units and peculiarities in translation. The translation of the expressions given in the article and their specific features are analyzed through various examples.